2022
DOI: 10.1002/hed.27119
|View full text |Cite
|
Sign up to set email alerts
|

Induction chemotherapy of modified docetaxel, cisplatin, 5‐fluorouracil for laryngeal preservation in locally advanced hypopharyngeal squamous cell carcinoma

Abstract: BackgroundPrevious studies have investigated the value of induction chemotherapy (IC) in organ preservation strategies for head and neck cancers. This study evaluated the effectiveness of sequential IC with radiotherapy as a laryngeal preservation strategy for locally advanced hypopharyngeal carcinoma (LAHSCC).MethodsOne hundred and forty‐two consecutive patients with LAHSCC were retrospectively analyzed who received three IC regimens from 2015 to 2019.ResultsIn the TP (docetaxel plus cisplatin), TPF (TP plus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…Multivariate Cox analysis revealed that volume, N stage, and rad-score were statistically significant predictors of OS. Compared to PR patients, non-PR patients had significantly worse OS (p = 0.01), which is consistent with previous studies showing that non-PR patients had a poor prognosis for LC (26). The prognostic significance also differed between the PR and non-PR groups in both cohorts, consistent with the results of previous studies (27,28).…”
Section: Discussionsupporting
confidence: 91%
“…Multivariate Cox analysis revealed that volume, N stage, and rad-score were statistically significant predictors of OS. Compared to PR patients, non-PR patients had significantly worse OS (p = 0.01), which is consistent with previous studies showing that non-PR patients had a poor prognosis for LC (26). The prognostic significance also differed between the PR and non-PR groups in both cohorts, consistent with the results of previous studies (27,28).…”
Section: Discussionsupporting
confidence: 91%
“…In previous study (Li et al, 2022), we have reported that modified TPF chemotherapy was an effective approach for laryngeal preservation in HPSCC. However, there were still 35%-45% of patients who showed no response after chemotherapy (Li et al, 2022).…”
Section: Introductionmentioning
confidence: 98%
“…In previous study (Li et al, 2022), we have reported that modified TPF chemotherapy was an effective approach for laryngeal preservation in HPSCC. However, there were still 35%-45% of patients who showed no response after chemotherapy (Li et al, 2022). In present study, we further identify the differentially expressed genes that are closely related to the TPF-chemotherapysensitivity (CS) in HPSCC by RNA sequencing.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Induction chemotherapy is the standard-of-care treatment for head and neck cancer [ 6 , 7 ]. In particular, docetaxel (DTX) is one common chemotherapy drug in the treatment of head and neck cancer [ 8 , 9 , 10 ] that is delivered via systemic intravenous [ 6 , 7 , 11 , 12 , 13 ] or locoregional intra-arterial [ 14 , 15 , 16 ] routes. Either delivery route has its own pros and cons that undermine the expected benefits of chemotherapy.…”
Section: Introductionmentioning
confidence: 99%